2018
DOI: 10.1021/acs.nanolett.8b00453
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Interference Assisted Spin Filtering in Graphene Nanoflakes

Abstract: We demonstrate that hexagonal graphene nanoflakes with zigzag edges display quantum interference (QI) patterns analogous to benzene molecular junctions. In contrast with graphene sheets, these nanoflakes also host magnetism. The cooperative effect of QI and magnetism enables spin-dependent quantum interference effects that result in a nearly complete spin polarization of the current and holds a huge potential for spintronic applications. We understand the origin of QI in terms of symmetry arguments, which show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 66 publications
4
65
0
Order By: Relevance
“…In our original proposal in Ref. 5, we showed that destructive QI can be used to generate nearly completely spin-polarized currents in the absence of magnetic fields or spin-orbit coupling, simply exploiting the spontaneous breaking of the SU (2) spin-rotational symmetry induced by electronic correlation in the presence of the edges. The present work extends the scope of our previous study to multi-component systems where other degrees of freedom (e.g., valley, orbital, layer) can be manipulated via an external handle lifting the symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our original proposal in Ref. 5, we showed that destructive QI can be used to generate nearly completely spin-polarized currents in the absence of magnetic fields or spin-orbit coupling, simply exploiting the spontaneous breaking of the SU (2) spin-rotational symmetry induced by electronic correlation in the presence of the edges. The present work extends the scope of our previous study to multi-component systems where other degrees of freedom (e.g., valley, orbital, layer) can be manipulated via an external handle lifting the symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In the PM state, the anti-resonance is pinned at the Fermi level ω QI = 0 due to the particle-hole symmetry of the spectrum. 5,58 In the AF state instead ω QI σ is spin-dependent and shifts below or above the Fermi level, proportionally to the average staggered magnetization S z . The detailed analysis of the transmission as a function of U/t shown in Fig.…”
Section: B Spin-split Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explore extensively the dependence of parameters we focus on finite artificial flakes, following previous calculations in a solid-state set-up [12,21]. We borrow from these works the choice to start from the 150-site cluster that we label as 5N (according to a notation where N is the number of sites on an edge).…”
Section: Model and Methodsmentioning
confidence: 99%
“…24,25 But only few reports have described QI effects in systems exhibiting spin polarization. [26][27][28][29] Recently, Li et al proposed a mechanism for tuning the spin filtering ratio based on QI effects in a nickel based junction. 30 Ratner and coworkers have demonstrated that how DQI features can be controlled by addition of a donor or acceptor group to the polyacetylene chain bridging graphene nanoribbons (ZGNR).…”
Section: Introductionmentioning
confidence: 99%